MEMAHAMI ETIKA BIROKRASI PUBLIK - Gabriel Lele (Jurnal Manajemen Kepegawaian, 2008)
This article investigates the problem of public service ethics from an institutional optic. This is an alternative way of looking at ethics other than a cultural approach. While acknowleding that ethics roots in culture, this article argues that ethics is institutionally embedded and can therefore be institutionally engineered. Since public service ethics is an integral part of a social contract between a government and its citizens, this article recommends the implementation of a contract-like mechanism to improve ethics in public service delivery. Citizen’s charter is among the alternatives for such purpose as citizens can control their government and hold it accoutable in process of service delivery.Key words: ethics, public service, control, citizen’s charter